Comparative Analysis of The Laws of Ṭahārah Between Chatsonic Artificial Intelligence and The Classical Islamic Text Fatḥ Al-Qarīb - Qoyyimah, Maysarotud Dinul; Sulaikho, Siti (Proceeding International Conference on Education, 2024)
Chatsonic is an advanced Artificial Intelligence technology that has been widely utilized by students and educators to facilitate learning processes. This study aims to evaluate the accuracy of Chatsonic in interpreting the concept of Ṭahārah based on the text Fatḥ al-Qarīb, analysing its strengths and weaknesses. This research employs a qualitative method with a descriptive approach. Data were collected from documents and analysed using the qualitative content analysis procedure developed by Philipp Mayring. The results show that while Chatsonic can explain certain aspects of Ṭahārah, there are several inaccuracies in its interpretation. For example, Chatsonic defines muṭlaq water as "pure water without any salt content", musyammas water as "water mixed with soil or dust", and musta’mal water as "water that can be reused for ablution". These definitions differ from the interpretation in Fatḥ al-Qarīb, where muṭlaq water is described as pure and purifying, without prohibition for use, musyammas water is pure and purifying but disliked for ritual purification, and musta’mal water is pure but cannot purify as it has already been used for ablution. This study provides further insight into the limitations of using AI technologies like Chatsonic to understand Islamic jurisprudence concepts, particularly in the context of Ṭahārah.